Extraction of Tannin Compounds from Samanea saman (Jacq.) Merr Leaves and Their Application as Corrosion Inhibitor in ST 37 Steel - S. Kasim; S. Fauziah; R. Ananda; I. W. Sutapa; A. Kamari (International Journal of Acta Material, 2024)
Research has been conducted on extracting tannin compounds from Samanea saman (Jacq) Merr leaves and their potential application as corrosion inhibitors for ST 37 steel. The purpose of this study was to evaluate the impact of adding Samanea saman (Jacq) Merr leaf extract on the corrosion rate and inhibition efficiency of ST 37 steel when exposed to 25% acetic acid. The immersion process was carried out with different concentrations: 0%, 5%, 10%, 20%, and 30%, and with immersion time intervals of 2, 4, 6, and 8 days. The concentration and optimum immersion time results were then further tested at temperatures of 20ºC, 30ºC, and 40ºC. The test results indicate that corrosion occurs uniformly on the surface of the steel. The corrosion rate was determined using the weight loss method, and it was observed that the weight reduction of the steel without inhibitor was higher compared to that of the steel treated with Samanea saman (Jacq) Merr leaf extract inhibitor. Based on the study findings, the highest inhibition efficiency was achieved with a concentration of 20% and an immersion time of 6 days, resulting in an efficiency of 87.3464% and a corrosion rate of 1.9143 mpy. Regarding temperature variations, the highest inhibition efficiency was observed at 20ºC, with an efficiency of 66.6908% and a corrosion rate of 2.8435 mpy.